The multidimensional profiling of youth male rugby union players: a systematic scoping review, nominal group technique and survey - Kay, E.; Till, K.; Shand, R.; Boyd, A.; Ramirez-López, C. (Journal of Sports Sciences, 2025)
This three-part study aimed to 1) investigate the most common profiling practices in male rugby union; 2) identify factors profiled within youth players; and 3) assess the importance of these factors for player progression and their measurement feasibility. Part one employed a systematic scoping review. For part two, expert practitioners participated in a Nominal Group Technique session to identify factors to profile within youth male rugby union. Part three included practitioners from a Tier One rugby nation and researchers, who ranked their agreement for the importance of the identified factors, and their measurement feasibility. The review identified 107 studies profiling 50 factors across five themes: physical (n = 67 studies), demographic (n = 25), psychological (n = 20), technical (n = 20), and tactical (n = 6). Expert practitioners reported an additional 20 factors that should be profiled. Over 70% of the survey participants agreed that 40 factors were important for progression and 28 factors were feasible to measure. Only 15 factors reached 70% agreement for both importance and feasibility, including strength, power, and games played. Factors across all themes were considered important, re-emphasising the need for multi-dimensional profiling within youth male rugby union. Further research is required to enhance the feasibility of measuring these factors and create a multidimensional player profile.